Performance Modeling of an Enhanced Optimistic Locking Architecture for Concurrency Control in a Distributed Database System - Akintola, A.A.; Aderounmu, G.A.; Osakwe, A.U.; Adigun, M.O. (Journal of Research and Practice in Information Technology, 2020)
Journal of Research and Practice in Information Technology, Volume 37, No. 4,p.365-380.